Low Dose of Beryllium Influences Gut Microbiota Promoting Metabolic Syndrome - Cha, Kwang-Hyun; YANG, JUNG-SEOK; Kyung-A; YOON KYE-YOON; Song Dae-geun; Erdenedolgor Erdene-Ochir; PAN CHEOL-HO; GwangPyo (Keystone Symposia, 2019)
Despite the considerable evidence that exposure to the environmental elements including minerals and metals could be significantly associated with host metabolic disorder, few studies have investigated the relationships among fecal elements, gut microbiota, and host metabolism. We analyzed 29 elements from 304 Korean twins feces and performed the correlation study among fecal elements, metabolic disorder, and gut microbiota. Fecal beryllium content was significantly correlated with the odds ratios for metabolic disease and had high relationships with the reduction of microbial species evenness. Akkermansia and Bifidobacterium, the metabolic syndrome-related gut microbiota, showed significant negative associations with beryllium. We assessed whether a low dose of beryllium exposure could affect gut microbial changes and promote metabolic syndrome using in vivo mice model. In mice fed a high-fat diet, 30 ppb of beryllium exposure resulted in significant body weight gain and increased plasma biomarkers for metabolic disorder. The beryllium exposure also caused the shifts in the gut microbial community with the microbial diversity reduction and the significant decrease of Akkermansia. In vitro human feces culture experiments also showed the reduction of species evenness and Bifidobacterium by the treatment of beryllium. The changes in cecal short chain fatty acids profiles (increase in acetate, but decrease in propionate and butyrate) in beryllium-exposed mice were related to appetite increase with a significant decrease in the anorexigenic hormone. The expression of inflammation-related genes and plasma lipopolysaccharide levels significantly increased in mice fed a high-fat diet with the exposure to beryllium.
Keywords: beryllium; microbiota; metabolic syndrome; fecal elements